Effects of dietary condensed tannins on small suminant productions - Priolo A.; Ben Salem H. (Nutrition and feeding strategies of sheep and goats under harsh climates, 2004)
This mini-review collates and discusses scientific information on the effects of condensed tannins (CT) on sheep productions, studied principally for temperate legume pastures in New Zealand. CT increases wool growth because it reduces protein degradation in the rumen, improving amino acids supply to, and absorption from, the small intestine. CT from Lotus corniculatus increased milk yield, protein and lactose percentages, and reduced fat percentage. CT have increased carcass leanness and reduced fatness, may be due to improved protein nutrition due to an increased flow of protein and essential amino acids to the intestine. CT from Acacia cyanophylla had no significant effects. Lean colour in meat was affected by CT from A. Cyanophyla and Ceratonia siliqua pulp, being darker when supplementing with polyethylene glycol (used to deactivate CT). This could be linked with a reduced myoglobin synthesis although iron absorption seems not to be affected by CT.
9. Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2001/11/08-10, Hammamet (Tunisia)